Impact Appraisal Of Investment Returns In The Disinvestment Backdrop: Empirical Evidence From Service Sector In Indian Cpses - Sudipta Ghosh; P.S. Aithal (Cita Konsultindo Research Center, 2022)
Abstract Investment is the procedure of allocating funds in order to produce earnings. In the process of investment, risk and return forms the two sides of a same currency. The term “investment return” is commonly used to compute the effectiveness of an investment. Alternatively, known as “Return on Investment” also helps to appraise the competency of diverse investments at a particular point of time. The focal goal of the cram is to appraise the brunt of investment income at aggregate level that are generated by the service sector in Indian CPSEs from 2010-11 to 2019-20. For this purpose, seven industries are considered on aggregative basis. To analyze the resultant data, both accounting and statistical tools are applied in the study. The results of the study reveal significant positive impact with respect to return on equity in the service sector. This implies that service sector has played an imperative role in the financial growth process of the economy. To earn more returns on investment, the Government should adopt necessary measures like minimization of preset interest cost obligation, efficient use of inner resources and optimization of outfitted efficiency. Key Words: Disinvestment, Impact, Indian CPSEs, Investment Returns, Service Sector.